Методологія chaos engineering у devops як засіб моделювання відмов у ci/cd для підвищення надійності систем - Матвєєв, М. С. (ХНУРЕ, 2025)
The present paper explores the potential of Chaos Engineering as a methodology for enhancing the reliability of software systems within the DevOps environment. Chaos Engineering facilitates the emulation of arbitrary failures within Continuous Integration/Continuous Delivery processes, thereby aiding in the identification of latent vulnerabilities prior to their actualisation. The paper delves into the foundational tenets of Chaos Engineering, examines prevalent instruments (Gremlin, LitmusChaos, Chaos Monkey), and investigates their implementation in cloud and containerised environments.
Keywords: chaos engineering; devops; моделювання відмов